PERANCANGAN SISTEM MUTU KINERJA KARYAWAN (Studi Kasus: PDAM TIRTA Khatulistiwa Pontianak) - Hendini, Ade; Kurnia, Syifa (STMIK KAPUTAMA, 2022)
The Tirta Khatulistiwa PDAM Pontianak office is a piped water / clean water office in Pontianak, which is located on the Imam Bonjol street in Pontianak, West Kalimantan, is a state-owned company. in the recap system the value of employees is still using a manual system. The current system is still using the Ms.Exel application, without a database. As a result of this many obstacles faced by the PDAM in the business of recapitating employee values such as the time needed to find or enter employee values requires a long time. In this thesis the software development method using the waterfall model is used to create an information system. The results of storing the performance value and means to see the quality value of employee performance. The system consists of 2 types of users, namely admin and employee. admin manages the value of employees and employees can see the value in the input admin. With the design of this system it is expected that this system is to design the system at PDAM Tirta Khatulistiwa as a means of overcoming the problem of inputting values at PDAM Tirta Khatulistiwa Pontianak.